NRBP2 Functions as a Tumor Suppressor and Inhibits Epithelial-to-Mesenchymal Transition in Breast Cancer - Li, Zhiyu; Liu, Bingxiong; Li, Chenyuan; Sun, Si; Zhang, Hanpu; Sun, Shengrong; Wang, Zhong; Zhang, Xiongjie (Frontiers in Oncology, 2021)
Nuclear Receptor Binding Protein 2 (NRBP2), one of the pseudokinases discovered during a screen of neural differentiation genes, inhibits tumor progression in medulloblastoma and hepatocellular carcinoma. However, the role and the mechanism of NRBP2 in the regulation of the progression of breast cancer (BC) have not been reported. In our study, NRBP2 was downregulated in human BC tissues compared with the corresponding normal tissues. Moreover, bioinformatics and cellular experiments illustrated that a lower level of NRBP2 contributed to a poor prognosis for patients with BC. In addition, we characterized the NRBP2-overexpressing BC cells and found that NRBP2 overexpression dramatically suppressed cell proliferation and invasion and inhibited the epithelial-mesenchymal transition (EMT) in cells in vitro, whereas knockdown of NRBP2 reversed these effects. Furthermore, overexpression of NRBP2 in the orthotopic breast tumor model significantly reduced lung metastatic nodules in nude mice. Mechanistically, NRBP2 regulated the activation of the 5′-adenosine monophosphate (AMP)-activated protein kinase/ mammalian target of rapamycin (AMPK/mTOR) signaling pathway. Moreover, the inhibition of cell proliferation, invasion and the EMT by NRBP2 overexpression was partially rescued after treatment with an AMPK inhibitor. Conversely, mTOR-specific inhibitors eliminated the effects of NRBP2 knockdown on increasing cell proliferation, invasion and the EMT, which suggested the anti-tumor effect of NRBP2, which may be partially related to the regulation of the AMPK/mTOR pathway. Taken together, NRBP2, a novel and effective prognostic indicator, inhibited the progression of BC and may become a potential therapeutic target for BC.